(untitled) (Comparative Professional Pedagogy, 2025)
The integration of Artificial Intelligence (AI) into English as a Foreign Language (EFL) education marks a significant transformation in pedagogical practices, particularly in higher education. In many European countries, such as Germany, Estonia, Finland, and Ukraine, this transformation is accelerating as education systems increasingly adopt AI technologies that replicate human cognitive processes like problem-solving and decision-making. They provide unprecedented opportunities for personalizing language learning based on individual student needs. This study explores current trends, pedagogical models, and empirical findings related to the implementation of AI in EFL classrooms, with particular attention to its impact on the development of language skills, learner autonomy, and affective factors such as motivation and engagement. Within the European context, these issues are especially relevant due to the widespread status of English as a foreign language and the strategic emphasis on digital innovation in national education systems. Drawing on both international and Ukrainian research, the study examines the application of widely used AI tools, such as chatbots, writing assistants, translation platforms, and intelligent tutoring systems, in language teaching. Empirical evidence, including findings from European-based studies, indicates significant improvements in students’ receptive (reading, listening) and productive (speaking, writing) language skills, lexical acquisition, and intercultural competence. Furthermore, AI enhances the affective dimension of learning by boosting motivation, promoting engagement, and alleviating foreign language anxiety through personalized, adaptive feedback and autonomous learning pathways. Despite these benefits, the integration of AI into EFL education is characterized by some challenges, including students’ over-reliance on technology, insufficient digital literacy among users, ethical concerns regarding data privacy, and a lack of comprehensive pedagogical frameworks. The study emphasizes the need for pre-service teacher training programs that effectively incorporate AI competencies. Overall, the study results indicate a positive impact of integrating AI into the teaching of English as a foreign language in European counties (including Ukraine), demonstrating how technological innovations can complement traditional pedagogical approaches to support accessible, effective, and learner-centered foreign language education in the digital era.